Race, Gender, and Deviance in Xbox Live: Theoretical Perspectives from the Virtual Margins - Gray, Kishonna L. (Anderson Pub., 2015)
Race, Gender, and Deviance in Xbox Live provides a much-needed theoretical framework for examining deviant behavior and deviant bodies within one of the largest virtual gaming communities—Xbox Live. Previous research on video games has focused mostly on violence and examining violent behavior resulting from consuming this medium. This limited scope has skewed criminologists' understanding of video games and video game culture. Xbox Live has proven to be more than just a gaming platform for users. It has evolved into a multimedia entertainment outlet for more than 20 million users. This book examines the nature of social interactions within Xbox Live, which are often riddled with deviant behavior, including but not limited to racism and sexism. The text situates video games within a hegemonic framework deploying whiteness and masculinity as the norm. The experiences of the marginalized bodies are situated within the framework of deviance as they fail to conform to the hegemonic norm and become victims of racism, sexism, and other types of harassment.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Diffusion of Innovation Theory and Xbox Live: Examining Minority Gamers' Responses and Rate of Adoption to Changes in Xbox Live - Gray, Kishonna L. (Bulletin of Science, Technology & Society, 2012)
This article examines the response of minority gamers as they adopt new innovations in Xbox Live. Using diffusion of innovation theory, specific attention is given to gamers’ rate of adoption of the new Xbox Live environment, which was a recent update to the Xbox Live interface. By employing virtual ethnography, observations, and interviews reveal that gaming duration and gender are significant factors in identifying a gamer’s successful rate of adoption of the new innovation. Female participants reveal that Xbox Live intentionally targets males as the default gamer and enact changes based on their needs. The research concludes with a plea to Xbox Live to acknowledge minority gamers such as women to incorporate their needs within the decision-making process of new innovations.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Gendered Play, Racialized Reality: Black Cyberfeminism, Inclusive Communities of Practice, and the Intersections of Learning, Socialization, and Resilience in Online Gaming - Richard, Gabriela T.; Gray, Kishonna L. (Frontiers, 2018)
In lieu of an abstract, here is a brief excerpt of the content: introduction While digital games hold promise for learning and socialization, emerging research and popular debates have critiqued inclusive access to these practices and literacies. This essay examines digital games for their potential to integrate diverse individuals and communities for learning and socialization, especially in online play and broadcasting of gameplay. For example, a level of cultural competency can be attained in well-developed games to overcome essentialist notions and assumptions about women and people of color. Using Black Cyberfeminism as a theoretical lens to make sense of players’ experiences, and Racialized Pedagogical Zones (RPZs) as an analytical frame to situate digital games’ entrenched ideologies of race and racism, we contend that games offer highly unproblematized depictions but have extreme potential for cultural competency. We further utilize Communities of Practice (CoP) as a frame for understanding and interrogating equitable access to community-supported collaborative learning and mastery within game culture, more broadly, and interest-driven guilds, clans, and affinity spaces, more specifically. In our extension of CoP, we integrate inclusive to highlight the resistive and resilient strategies employed by supportive communities for diverse women in addressing the systematic nature of oppression and power relations that undergird communities of practice, particularly in marked gendered spaces such as gaming. Marginalizing practices in game culture have become more widely publicized and understood in recent years, most notably because of high profile incidents of harassment. However, representations of women and racial or ethnic minorities by the gaming industry have also been problematic historically. For instance, since the 1980s video games have been critiqued for the hypersexualization of women and women are often the victims of misogynistic [End Page 112] vitriol, as the incidents around Gamergate have exposed. People of color are featured in largely stereotypical ways and are all but absent from the gaming industry. Queer gamers and gamers with dis/abilities are almost entirely absent and, when present, are not depicted fairly. This differential treatment appears to have a symbiotic relationship with the exclusion of marginalized players. As researchers have noted, Internet technologies and virtual communities operate in a manner that benefits privileged identities. These unequal power relations are accepted as legitimate and are embedded in the cultural practices of digital technology. Nevertheless, many gamers—most notably women—have resisted this perpetual state of inequity and the dominant narrative of power, control, and exclusion. Although some in gaming contend that these are not overt practices of exclusion, many players and scholars acknowledge the existence of symbolic exclusion, where those who are valued have the privilege to define legitimate practice and participation within gaming culture. The unequal power relations operating within the gaming community influence not only what gamers consume but also what they learn about themselves and others. Further, the racialized and gendered consumptive practices through gaming are often taken for granted. Commercial gaming culture is, with few exceptions, complicit in these exclusionary practices by continuing to design at a deficit, despite these increasingly apparent realities. But many gamers have begun to resist and challenge not only the imagery but also the practices that sustain white, masculine privilege within gaming and technology in general. While these practices have yet to reach a critical mass to disrupt the power structure operating within game culture as a whole, they exist counter to the mainstream and empower the marginalized operating within them. While the literature will provide an overview of these practices, our purpose is to privilege the resistance and resilience strategies of the marginalized to disrupt the traditional narrative while they empower themselves. We utilize Kimberlé Crenshaw’s framework of intersectionality to reflect on identity, recognizing that “the problem with identity politics is not that it fails to transcend difference, as some critics charge, but rather the opposite—that it frequently conflates or ignores intragroup differences.” We also want to caution that while we focus on players who have historically been the marginalized in gaming culture and game research, we recognize that men...
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Feminism in Play - Gray, Kishonna L.; Voorhees, Gerald; Vossen, Emma (Palgrave Macmillan, 2018)
Feminism in Play focuses on women as they are depicted in video games, as participants in games culture, and as contributors to the games industry. This volume showcases women's resistance to the norms of games culture, as well as women's play and creative practices both in and around the games industry. Contributors analyze the interconnections between games and the broader societal and structural issues impeding the successful inclusion of women in games and games culture. In offering this framework, this volume provides a platform to the silenced and marginalized, offering counter-narratives to the post-racial and post-gendered fantasies that so often obscure the violent context of production and consumption of games culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé